2016
DOI: 10.3390/nano6090154
|View full text |Cite
|
Sign up to set email alerts
|

Inverter Circuits Using ZnO Nanoparticle Based Thin-Film Transistors for Flexible Electronic Applications

Abstract: Innovative systems exploring the flexibility and the transparency of modern semiconducting materials are being widely researched by the scientific community and by several companies. For a low-cost production and large surface area applications, thin-film transistors (TFTs) are the key elements driving the system currents. In order to maintain a cost efficient integration process, solution based materials are used as they show an outstanding tradeoff between cost and system complexity. In this paper, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Oxide semiconductors such as ZnO do not form an insulating layers at the NP surfaces when dispersed in water and/or handled in the air, which make it easy to TFT fabrication process. Therefore, many efforts have been made to form and demonstrate TFTs with the n-type ZnO-NP channels on various substrates [1, 6−12] including demonstration of the logic operations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Oxide semiconductors such as ZnO do not form an insulating layers at the NP surfaces when dispersed in water and/or handled in the air, which make it easy to TFT fabrication process. Therefore, many efforts have been made to form and demonstrate TFTs with the n-type ZnO-NP channels on various substrates [1, 6−12] including demonstration of the logic operations [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various authors have investigated the properties of three-layer TCO films with oxide/metal/oxide or metallic oxide/metal/metallic oxide structures [21]. The results have shown that such films not only suppress the reflection from the metallic layer in the visible light range but also produce a transmittance effect [22,23]. Consequently, the TCO thin films are used in solar cells, gas sensors, LCD displays, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide-based inverters, which are the basic building blocks in both digital and analog circuits, have been intensively studied for phase reversals, amplifications, wave shaping, etc. Up to date, most reported inverters based on oxide semiconductors were composed by two n-type oxide thin-film transistors (TFTs) [3][4][5][6][7][8], due to the lack of high-performance p-type oxide TFTs. These inverters generally show a low voltage gain mainly due to their weak ability of logic pull-up.…”
Section: Introductionmentioning
confidence: 99%